New Perspectives for Spinal Cord Stimulation in Parkinson’s Disease-Associated Gait Impairment: A Systematic Review - Christian G. Seufert; Matthias C. Borutta; Martin Regensburger; Yining Zhao; Thomas Kinfe (Biomedicines, 2024)
Parkinson’s Disease is a neurodegenerative disorder manifesting itself as a hypokinetic movement impairment with postural instability and gait disturbance. In case of failure and/or limited response, deep brain stimulation has been established as an alternative and effective treatment modality. However, a subset of PD patients with gait impairment represents a therapeutic challenge. A systematic review (2000–2023) was performed using PubMed, Embase, Web of Science, Scopus, and Cochrane Library databases to determine the efficacy, stimulation waveform/parameters, spine level, and outcome measures of spinal cord stimulation using different waveforms in PD patients with and without chronic pain. Spinal cord stimulation responsiveness was assessed within the pre-defined follow-up period in three groups (short-term follow-up = 0–3 months; intermediate follow-up = 3–12 months; and long-term follow-up = more than 12 months). In addition, we briefly outline alternative neurostimulation therapies and the most recent developments in closed-loop spinal cord stimulation relevant to PD. In summary, 18 publications and 70 patients from uncontrolled observational trials were included, with low-quality evidence and conflicting findings. First and foremost, the currently available data do not support the use of spinal cord stimulation to treat PD-related gait disorders but have confirmed its usefulness for PD-associated chronic pain.